The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/ijph-08-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

A rapid systematic review of what we know about alcohol use disorders and brief interventions in the criminal justice system

Abstract: Purpose – The purpose of this paper is to review the evidence of alcohol use disorders within the different stages of the criminal justice system in the UK. Furthermore it reviewed the worldwide evidence of alcohol brief interventions in the various stages of the criminal justice system. Design/methodology/approach – A rapid systematic review of publications was conducted from the year 2000 to 2014 regarding the prevalence of alcohol use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 36 publications
1
40
1
Order By: Relevance
“…Also, limited rigorous research bearing on the use of SBIRT with offenders is available, whether for alcohol use or illicit drug use (for a recent review of brief interventions for alcohol use disorders in the criminal justice system, see Newbury-Birch et al, 2016). Two randomized studies indicate that brief intervention did lead to positive change among probationers, either for alcohol (Wells-Parker & Williams, 2002) or for alcohol and drugs (Davis et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Also, limited rigorous research bearing on the use of SBIRT with offenders is available, whether for alcohol use or illicit drug use (for a recent review of brief interventions for alcohol use disorders in the criminal justice system, see Newbury-Birch et al, 2016). Two randomized studies indicate that brief intervention did lead to positive change among probationers, either for alcohol (Wells-Parker & Williams, 2002) or for alcohol and drugs (Davis et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, prevalence data from a rapid systematic review showed that 53-69% of adults in the probation setting scored positively for an alcohol use disorder. 9 Both of these behaviours (which are often co-existing) lead to several health problems, and possibly low mental well-being, through a number of plausible processes (e.g. economic, social, psychological).…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…A more recent rapid systematic review identified no UK studies and only three from the USA of which none was remand focused. 10 Likewise, to our knowledge there are no evaluation studies of ABIs involving male remand prisoners in the UK.…”
Section: Introductionmentioning
confidence: 98%